The Interrelations of Family Relationship, Illness Cognition of Helplessness and Perceived Barriers to Medication Adherence: A Study of Adolescent and Emerging Adult Kidney Recipients and Their Parents - Hamama-Raz Y; Frishberg Y; Ben-Ezra M; Levin Y (Dove Medical Press, 2023)
Yaira Hamama-Raz,1 Yaacov Frishberg,2 Menachem Ben-Ezra,1 Yafit Levin1 1School of Social Work, Ariel University, Ariel, Israel; 2Division of Pediatric Nephrology, Shaare Zedek Medical Center, Faculty of Medicine, Hebrew University of Jerusalem, Jerusalem, IsraelCorrespondence: Yaira Hamama-Raz, Email yairahr@ariel.ac.ilBackground: Medication adherence among adolescents and emerging adults following kidney transplantation was found to be lower with harmful consequences. The current study aimed to examine associations between illness cognition of helplessness, family relationships, and perceived barriers to medication adherence among post-kidney transplant adolescent and emerging adult recipients and their parents by applying a dyadic perspective.Methods: Fifty-nine dyads of adolescents and emerging adults aged 11- 26 years and their parents, were recruited from a pediatric nephrology department in a medical center in Israel. Both adolescents and emerging adults and parents completed self-report questionnaires addressing illness cognition of helplessness (subscale of Illness Cognition Questionnaire), family relationships related to conflict and cohesion (Brief Family Relationship Scale), and the adolescents' perceived barriers (Adolescent Medication Barriers Scale) to taking their prescribed medications.Results: Adolescents' and emerging adults' perceptions of family conflicts moderated the link between illness cognition of helplessness among parents and barriers to medication adherence via the illness cognition of helplessness among adolescents and emerging adults. However, only the adolescents' and emerging adults' perceptions of family cohesion had a direct association with barriers to medication adherence. Parents' perceived family conflict and cohesion did not directly associate with barriers to medication adherence. Findings highlight the complex interplay between family dynamics, illness cognition, and barriers to medication adherence in adolescents and emerging adults.Conclusion: Parents', adolescents' and emerging adults' perceptions of family conflicts and cohesion, as well as their illness cognitions, can play important roles in understanding and addressing barriers to medication adherence in this population. The study reveals findings that highlight the dyadic transference process of illness cognition of helplessness among both adolescent and emerging adult kidney recipients and their parents in assessing barriers to medical treatment.Keywords: illness cognition of helplessness, family relationships, barriers to medication adherence, adolescents, parents, kidney transplantation